The Convexity of Families of Adjoint Patches for a Bezier Triangular Surface (Journal of Computational Mathematics, 2021)
A necessary and sufficient condition for the convexity of adjoint patches for a Bezier triangular surface is presented. Furthermore, it is proved that this condition is equivalent to the fact that the adjoint patches form a decreasing sequence as the corresponding degree decreases. The condition can be easily computationally verified.